Personality Traits and Performance of Immigrant-Owned Small Businesses - Fatoki, Olawale (Journal of Reviews on Global Economics, 2020)
Motivation: Immigrant entrepreneurs contribute to employment and the sustainable growth of host countries and both native and immigrant-owned enterprises should be included in the growth and employment strategy of a country. However, immigrant-owned small businesses face many challenges which impact on their performance and survival. The personality traits of immigrant entrepreneurs can influence the strategy adopted and implemented to improve business performance. Novelty: The aim of the study is to examine the effect of owners’ personality traits on the performance of immigrant-owned small businesses using the Five-Factor model. Empirical studies that specifically focus on the effect of personality traits on the performance of immigrant-owned small businesses are scarce. Methodology and Methods: The cross sectional survey method was used for data collection in a quantitative study. Data was collected from one hundred and ninety-six immigrant entrepreneurs and the participants in the survey were conveniently sampled. The participants of this study were in the retail and service businesses and were immigrants with legal residency in South Africa. Data and Empirical Analysis: The Partial Least Square Structural Equation Modelling (PLS SEM) was used for analysis. The results indicated significant positive relationships between three personality traits (openness to experience, conscientiousness, extraversion) and the performance of immigrant-owned small businesses. The influence of agreeableness is insignificant while the effect of neuroticism is significantly negative. Policy Considerations: The findings this study can help individuals, businesses and government agencies that support small businesses to understand the personality traits that can help to improve the performance of immigrant-owned businesses. The design of training programme to improve the performance of immigrant-owned businesses should include how to enhance the personality traits of immigrant entrepreneurs especially openness to experience, conscientiousness and extraversion. The employment strategy of immigrant-owned small businesses should focus on individuals with these performance-enhancing personality traits.